Therapeutic potential of mGluR5 targeting in Alzheimer's disease - Kumar, Anil; Dhull, Dinesh K.; Mishra, Pooja S. (Frontiers in Neuroscience, 2015)
Decades of research dedicated towards Alzheimer's disease (AD) has culminated in much of the current understanding of the neurodegeneration associated with disease. However, delineating the pathophysiology and finding a possible cure for the disease is still wanting. This is in part due to the lack of knowledge pertaining to the connecting link between neurodegenerative and neuroinflammatory pathways. Consequently, the inefficacy and ill-effects of the drugs currently available for AD encourage the need for alternative and safe therapeutic intervention. In this review we highlight the potential of mGluR5, a metabotropic glutamatergic receptor, in understanding the mechanism underlying the neuronal death and neuroinflammation in AD. We also discuss the role of mGlu5 receptor in mediating the neuron-glia interaction in the disease. Finally, we discuss the potential of mGluR5 as target for treating AD.